The long-term influence of hospital and surgeon volume on local control and survival in the randomized German Rectal Cancer Trial CAO/ARO/AIO-94 - Sprenger, Thilo; Beissbarth, Tim; Sauer, Rolf; Tschmelitsch, Joerg; Fietkau, Rainer; Hohenberger, Werner; Staib, Ludger; Raab, Hans-Rudolf; Roedel, Claus; Ghadimi, Michael (Surgical Oncology-Oxford, 2020)
Background: The association of treatment volume and oncological outcome of rectal cancer patients undergoing multidisciplinary treatment is subject of an ongoing debate. Prospective data on long-term local control and overall survival (OS) are not available so far. This study investigated the long-term influence of hospital and surgeon volume on local recurrence (LR) and OS in patients with locally advanced rectal cancers.
CRIS-Team WoS Importer:2021-01-08